2022
DOI: 10.3390/ijms23179819
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of Novel CRHR2 Gene Variants in Type 2 Diabetes and Depression

Abstract: The corticotropin-releasing hormone receptor 2 (CRHR2) gene encodes CRHR2, contributing to the hypothalamic–pituitary–adrenal stress response and to hyperglycemia and insulin resistance. CRHR2−/− mice are hypersensitive to stress, and the CRHR2 locus has been linked to type 2 diabetes and depression. While CRHR2 variants confer risk for mood disorders, MDD, and type 2 diabetes, they have not been investigated in familial T2D and MDD. In 212 Italian families with type 2 diabetes and depression, we tested 17 CRH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
(71 reference statements)
1
5
0
Order By: Relevance
“… 24 , 34 , 35 In animal and clinical trials, it is found that hyperglycemia may affect patients’ mood and behavior by affecting the hippocampus and amygdala, 36 , 37 the hypothalamus and its nucleus accumbens, 38 the HPA axis, 39 and MDD and hyperglycemic co-morbidity genes. 40 We also observed that waist circumference, other metabolic index levels and blood pressure were also higher in the hyperglycemic group than in the non-hyperglycemic subgroup, which is similar to the results of some previous studies, 21 , 34 suggesting that the overall metabolic level of patients with comorbid hyperglycemic MDD was disturbed, and interactions between different metabolic disorders have been found. 25 , 41–49 We also found that the hyperglycemic subgroup had a shorter duration of disease and a lower level of education.…”
Section: Discussionsupporting
confidence: 90%
“… 24 , 34 , 35 In animal and clinical trials, it is found that hyperglycemia may affect patients’ mood and behavior by affecting the hippocampus and amygdala, 36 , 37 the hypothalamus and its nucleus accumbens, 38 the HPA axis, 39 and MDD and hyperglycemic co-morbidity genes. 40 We also observed that waist circumference, other metabolic index levels and blood pressure were also higher in the hyperglycemic group than in the non-hyperglycemic subgroup, which is similar to the results of some previous studies, 21 , 34 suggesting that the overall metabolic level of patients with comorbid hyperglycemic MDD was disturbed, and interactions between different metabolic disorders have been found. 25 , 41–49 We also found that the hyperglycemic subgroup had a shorter duration of disease and a lower level of education.…”
Section: Discussionsupporting
confidence: 90%
“…As both CRHR1 and CRHR2 are expressed on the surface of mammalian ovaries and mediate CRH actions on ovulation and steroid biosynthesis [ 21 ], this repressed gene activation in the ovaries might impair the signaling essential for the female cycle regulation, steroid synthesis, follicles maturation, and ovulation phase, and contribute to the anovulatory cycles typical of PCOS. However, given that 7 of the CRHR1 -risk variants are in 2 LD blocks linked to T2D and MDD (unpublished data) and the same PCOS-risk alleles of 4 variants are significantly linked and associated with T2D, we can not a priori exclude that the mental-metabolic contribution risk, at least for these variants, might underlie the PCOS-related maladaptive stress response [ 11 ] and the increased blood cortisol levels found in 50% PCOS patients [ 13 , 32 ], which, as we previously hypothesized [ 33 ] and recently reported for CRHR2 [ 29 ], might per se contribute to T2D and MDD as well. Furthermore, T2D and MDD are comorbid with PCOS [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 88%
“…The corticotropin-releasing hormone receptors are essential components of the HPA axis which mediates the stress response and could potentially be implicated in stress and/or cortisol related pathologies [ 17 ]. We recently reported CRHR2 [ 29 ] as novel risk gene in the comorbidity of T2D and major depressive disorder (MDD). In this study, we report the novel linkage and association of the two corticotropin-releasing hormone receptors genes ( CRHR1 and CRHR2 ) with the risk of PCOS in multigenerational Italian families.…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding components throughout the HPA can therefore be considered candidate genes for mood disorders (e.g., depression) and metabolic abnormalities (e.g., type 2 diabetes). We have previously reported that the CRHR2 [ 28 ] and the melanocortin receptor genes ( MC1R - MC5R ) [ 29 ] are linked to and associated with the comorbidity of T2D and MDD. In this study, we extended this linkage and association to the glucocorticoid receptor gene ( NR3C1 ), which is an important component of the cortisol pathway.…”
Section: Discussionmentioning
confidence: 99%